Canon EOS Rebel T3i/600D for dummie - King, Julie Adair (John Wiley & Sons, 2011)
Whether it's your first dSLR, your first Canon camera, or simply a new tool for your photography, your Canon Rebel T3i/600D has countless capabilities and you'll want to understand them all. This book covers all the dials, menus, and controls, showing you how to use each one. It explains how to change and use various lenses and offers advice on exposure, focus, printing, using flash, sharing photos online, and much more, all with plenty of full-color examples to show what you can achieve.